2019
DOI: 10.3390/ijerph16122196
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Behavior of Three Fungicides during the Industrial Processing of Paeoniae Radix Alba and Associated Processing Factors

Abstract: Before being administered as medicinal products, Chinese herbal medicines (CHMs) must be processed and decocted for human consumption. While the presence of pesticide residues in CHMs is a major concern, pesticide dissipation behavior during CHM processing has rarely been reported. In this study, the dissipation of three pesticide residues in the CHM Paeoniae Radix Alba (PRA) was investigated during each step of industrial processing. The boiling process was found to significantly reduce pesticide residues (61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…PF may be more meaningful and could provide a more accurate basis for risk assessment when the residue concentrations change during the processing steps. It is known that routine processing steps, including washing, peeling, blanching, juicing, fermentation and distillation, could decrease the food amounts of pesticide residues [ 10 , 11 ]. Hakme et al [ 12 ] studied the PF values during baking for 41 pesticides in cereal bran-based biscuits.…”
Section: Introductionmentioning
confidence: 99%
“…PF may be more meaningful and could provide a more accurate basis for risk assessment when the residue concentrations change during the processing steps. It is known that routine processing steps, including washing, peeling, blanching, juicing, fermentation and distillation, could decrease the food amounts of pesticide residues [ 10 , 11 ]. Hakme et al [ 12 ] studied the PF values during baking for 41 pesticides in cereal bran-based biscuits.…”
Section: Introductionmentioning
confidence: 99%
“…Aguilera et al reported that heating for 30 min did not reduce the concentration of AZOX in zucchinis when considering water loss during cooking. Overall, depending on the cooking methods, both apparent decreases and increases in the AZOX concentrations (−92 to +60%) have been reported after heating. To date, the fate of nanoencapsulated AZOX during thermal processing has not been reported. In this context, it appears essential to identify TDPs for both conventional and nanoencapsulated AZOX to produce comprehensive risk assessments.…”
Section: Introductionmentioning
confidence: 99%